2021
DOI: 10.1080/13669877.2020.1871057
|View full text |Cite
|
Sign up to set email alerts
|

What drives risk perceptions? Revisiting public perceptions of food hazards associated with production and consumption

Abstract: As food technology continues to advance, the potential for new food products to enter the food market grows, attracting considerable media interest. Whilst previous research has explored public perceptions of food-related hazards, much of this took place over 10 years ago. Continued technological developments have yielded new food products, for which there is no extant research on public perceptions. In light of this, there is a pressing need to update and extend research exploring public perceptions of food-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 54 publications
0
24
0
4
Order By: Relevance
“…However, those responses with less than 15% missing data were treated by replacing the missing values with the mean ones, as Jenkins et al [ 20 ] suggested. Subsequently, the data were analyzed using the method outlined in [ 20 , 21 , 44 , 45 ]. The screening process has brought the final sample to 345 valid responses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, those responses with less than 15% missing data were treated by replacing the missing values with the mean ones, as Jenkins et al [ 20 ] suggested. Subsequently, the data were analyzed using the method outlined in [ 20 , 21 , 44 , 45 ]. The screening process has brought the final sample to 345 valid responses.…”
Section: Resultsmentioning
confidence: 99%
“…The second part of the analysis was conducted using disaggregate-level or hazard-focused analyses. Hence, a series of eight multiple regression analyses using non-aggregated data were conducted to test if the selected qualitative risk characteristics were significant predictors of the participants’ perceived risk [ 21 , 27 ]. Table 4 summarizes the multiple regression analysis results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of a pandemic, the perception of risk could be based on objective data, such as the number of people infected and deaths, but even more on the Perceived risk of COVID-19 on consumers subjectivity of individuals due to the uncertainty, anxiety and fear produced by the difficulties in controlling the pandemic and its serious consequences (Yildirim and G€ uler, 2020). Numerous studies have used the psychometric paradigm to explain the risk perception of hazards (Bonnet et al, 2012), which consists of two dimensions to assess risk perception in such situations: unknown risk and dread risk (Jenkins et al, 2021). With the aim of avoiding ambiguities, researchers have reframed these dimensions as cognitive and emotional/ affective (Yildirim and G€ uler, 2020).…”
Section: Perceived Risk Of Covid-19mentioning
confidence: 99%